Development of integrated pest management approaches against Helicoverpa armigera (Hubner) in tomato - Rahman, AKM Z; Haque, MA; Alam, SN; Begum, K; Sarker, D (Bangladesh Journal of Agricultural Research, 2016)
Five IPM packages viz. T1=Pheromone trap @ 70 traps ha-1 + Neem seed kernel extract @ 50 g L-1 of water; T2=Pheromone trap + HaNPV @ 0.4 ml L-1 of water and Bt @ 2.0 g L-1 of water; T3=Pheromone trap + Neem seed kernel extract + HaNPV and Bt; T4=Pheromone trap + Trichogramma chillnis @ 50,000 ha-1 and Bracon hebetor @ 1200 ha-1; T5=Pheromone trap + Neem seed kernel extract + T. chilonis and B. hebetor were evaluated against H. armigera in tomato. The lowest fruit infestation by number (12.55%) was attained from T5 followed by T2 (15.49%). Significantly the lowest fruit infestation by weight was found in treatment T2 (10.60%) followed by T5 (11.73%). The highest yield was obtained from T5 (29.74 t ha-1) followed by T2 (26.77 t ha-1). The highest marginal benefit cost ratio was achieved from T2 (3.41) followed by T5 (3.35). Hence, considering benefit cost ratio, T2 and T5 packages may be the effective tools for managing H. armigera in tomato. Bangladesh J. Agril. Res. 41(2): 287-296, June 2016